2005
DOI: 10.1017/s0022112004002277
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of large-scale coherence in a turbulent boundary layer using two-point correlations

Abstract: Stereoscopic particle image velocimetry (PIV) measurements are made in streamwisespanwise and inclined cross-stream planes (inclined at 45 • and 135 • to the principal flow direction) of a turbulent boundary layer at moderate Reynolds number (Re τ ∼ 1100). Two-point spatial velocity correlations computed using the PIV data reveal results that are consistent with an earlier study in which packets of hairpin vortices were identified by a feature-detection algorithm in the log region, but not in the outer wake re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
160
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 41 publications
(70 reference statements)
44
160
1
Order By: Relevance
“…Streamwise velocity correlations in the crossflow plane show clear evidence of large-scale streamwise structure such as those observed by Ganapathisubramani et al (2005) and Hutchins & Marusic (2007) in the log region of boundary layers on smooth walls. The existence of large streamwise structures over fully rough walls has already been noted by Hutchins & Marusic (2007).…”
Section: Discussionmentioning
confidence: 57%
“…Streamwise velocity correlations in the crossflow plane show clear evidence of large-scale streamwise structure such as those observed by Ganapathisubramani et al (2005) and Hutchins & Marusic (2007) in the log region of boundary layers on smooth walls. The existence of large streamwise structures over fully rough walls has already been noted by Hutchins & Marusic (2007).…”
Section: Discussionmentioning
confidence: 57%
“…The streamwise-elongated nature of p uu in smooth-wall turbulence has been previously linked to the low-momentum regions generated by hairpin vortex packets and the negative correlation outboard of the positive region in the spanwise direction represent the imprint of spanwisealternating low-and high-momentum regions. [47,48] In addition, Wu and Christensen [48] recently reported similar characteristics of p uu for flow over irregular roughness near the outer edge of the roughness sublayer, supporting the relative immunity of these vortical structures as well as their coherent organization into larger-scale structural entities to roughness. The present results lend additional support to the contention that hairpin vortex packets exist in rough-wall turbulence as well, including at the wall-normal position of the present measurements (y = 0.0475) which is deep within the roughness sublayer where roughness effects are most dramatic.…”
Section: Two-point Velocity Correlation Coefficientsmentioning
confidence: 81%
“…There exist a number of investigations on the literature about the coherent structures behind circular or finned tubes and also there are other studies investigating the three-dimensionality of structures. Ganapathisuramani et al [21] showed how stream-wise autocorrelation can be used to measure the size of stream-wise structures. Hutchins et al [22,23] used two-point span-wise correlation to obtain statistical information regarding the width and spacing of the coherent structures.…”
Section: Introductionmentioning
confidence: 99%